2010
DOI: 10.1103/physreva.81.062102
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing quantum discord in2×Nsystems

Abstract: Bipartite states with vanishing quantum discord are necessarily separable and hence positive partial transpose (PPT). We show 2 × N states satisfy additional property: the positivity of their partial transposition is recognized with respect to the canonical factorization of the original density operator. We call such states SPPT (for strong PPT). Therefore, we provide a natural witness for a quantum discord: if a 2 × N state is not SPPT it must contain nonclassical correlations measured by quantum discord. It … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 39 publications
2
76
0
1
Order By: Relevance
“…Nevertheless, one can swap the role of A and B and get another expression [28] for quantum discord as…”
Section: Quantum Discordmentioning
confidence: 99%
“…Nevertheless, one can swap the role of A and B and get another expression [28] for quantum discord as…”
Section: Quantum Discordmentioning
confidence: 99%
“…When considering an initial entangled state exposed to * E-mail: huyaohua1@sina.com local noisy environments, the entanglement may decrease abruptly and nonsmoothly to zero in a finite time, which is called entanglement sudden death (ESD) [5][6][7]. However, recent researches have shown that entanglement is not the only measure of quantum correlation, and a new but promising candidate is the quantum discord [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Quantum discord, first introduced by Ollivier and Zurek [16], is defined as the difference between the total correlation and the classical correlation with the following expression (ρ AB ) = (ρ AB ) − (ρ AB )…”
Section: Introductionmentioning
confidence: 99%
“…Recently various methods to detect zero-discord [28][29][30] have been proposed for a given state as well as for an unknown state [31]. Moreover, it is found that vanishing quantum discord is related to the complete positivity of a map [32] and the local broadcasting of quantum correlations [15].…”
Section: Introductionmentioning
confidence: 99%